A COMMUNICATIVE PROJECT-BASED LEARNING (CPBL) FRAMEWORK FOR ENHANCING TECHNICAL ENGLISH IN HIGHER EDUCATION (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The increasing demand for engineers and technical specialists with proficient English communication skills presents a significant challenge for higher education institutions. Traditional language teaching methods often fail to bridge the gap between theoretical knowledge and practical application in a professional context. This paper proposes a novel pedagogical framework, “Communicative Project-Based Learning” (CPBL), designed specifically to enhance technical English proficiency in higher education, with a particular focus on engineering and technology disciplines. Rooted in a comprehensive model of communicative competence, the CPBL framework synergizes established pedagogical strategies with modern, project-centric learning. It positions practical, real-world projects as the core learning experience, requiring students to collaboratively engage in technical tasks where the use of English for communication, problem-solving, and presentation is both necessary and natural.